2020
DOI: 10.1245/s10434-019-08092-2
|View full text |Cite
|
Sign up to set email alerts
|

Primary Tumor Surgery for Patients with De Novo Stage IV Breast Cancer can Decrease Local Symptoms and Improve Quality of Life

Abstract: Background. It was unknown whether surgery for primary tumor would affect the occurrence of local symptoms caused by tumor progression in patients with de novo stage IV breast cancer (BC). Our work attempted to probe the effect of local resection on controlling local symptoms and improving the quality of life in de novo stage IV BC patients. Methods. Our study included patients presenting with de novo stage IV BC at the Cancer Hospital of the Chinese Academy of Medical Sciences from January 2008 to December 20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 20 publications
0
18
0
1
Order By: Relevance
“…According to the E2018 trial, although surgery reduced the proportion patients with local regional recurrence or progression in three years, it did not improve health-related quality of life [23]. However, a retrospective analysis from China suggested that the quality of life in patients with de novo stage IV BC can be improved by reducing the incidence of local symptoms through primary tumor surgery [28]. Several cases have reported that LRT could solve local problems, improve the quality of life of patients, and reduce the psychological pressure of advanced BC [29].…”
Section: Discussionmentioning
confidence: 99%
“…According to the E2018 trial, although surgery reduced the proportion patients with local regional recurrence or progression in three years, it did not improve health-related quality of life [23]. However, a retrospective analysis from China suggested that the quality of life in patients with de novo stage IV BC can be improved by reducing the incidence of local symptoms through primary tumor surgery [28]. Several cases have reported that LRT could solve local problems, improve the quality of life of patients, and reduce the psychological pressure of advanced BC [29].…”
Section: Discussionmentioning
confidence: 99%
“…Copyright © Jiayu Wang GMR.000609. 5 (2).2020 that of ductal subtype, to metastasize in stomach with incidence of 69.1%. The luminal subtype was supposed to hold the foremost rate of 92.1% and triple-negative (TN) also had a risk of 7.9%, while gastric metastasis was not documented to occur in HER2 enriched subtype (Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Copyright © Jiayu Wang GMR.000609. 5 (2).2020 and CYFRA21-1 9.85ng per milliliter (0.0-3.3). Test for hepatitis B, hepatitis C, syphilis and human immunodeficiency virus were negative.…”
Section: Case Reportmentioning
confidence: 99%
See 1 more Smart Citation
“…De novo metastatic breast cancer (dnMBC) refers to patients with metastatic breast cancer at initial diagnosis, and has been reported that approximate 10% of newly diagnosed breast cancer patients present with distant metastases [1][2][3] . This group of patients with dnMBC makes up about 3-8% of new breast cancer diagnoses in the USA and Western [1,4] , and 3-5% of these patients in China [5] . Their overall survival (OS) was approximately 16 to 29 months [6] .…”
Section: Introductionmentioning
confidence: 99%